=
Note: Conversion is based on the latest values and formulas.
Integrate sin^2(x) - MyTutor In this case we want an identity which will relate sin^2(x) to a function we can integrate. A little thought tells us that the cosine double angle formula helps. This is cos(2x)=1-2sin^2(x). …
Integrate 4/x^2 - MyTutor First of all, I would ask the tutee if they were familiar with the law of integration. i.e. that you increase the power of the variable (x) by 1, then divide by the new power, and if not then I …
Expand and simplify (x-2)(x-4) - MyTutor One of the methods to answer this question would be the FOIL methodFirst Outer Inner LastStart by multiplying the First terms in each bracket and then the Outer and so on with Inner and …
Solve x^2 - 6x + 8 < 0 | MyTutor The x^2 - 6x + 8 equation is often written as equal to y. This is called a Quadratic Equation. ( x^2 - 6x + 8 = y). Our next step is to set this quadratic equation to 0 (i.e. y=0). We then factorise the …
Solve the simultaneous equations: x+y =2; x^2 + 2y = 12 So out second equation: x^2 + 2y = 12, becomes: x^2 + 2(2-x) = 12, expanding out the brackets we get: x^2 -2x +4 = 12, and take away 12 from both sides which will give us: x^2 - 2 - 8 = 0. …
Expand and simplify 3(2x + 5) – 2(x – 4) - MyTutor Expand and simplify 3(2x + 5) – 2(x – 4) Firstly, to expand an equation like this, you must multiply the brackets by the number outside of the brackets. Make sure that you multiply every number …
Solve: x/x+4 + 7/x-2 = 1 (Must show working)[4 marks] - MyTutor (x(x-2) + 7(x+4) )/ (x+4)(x-2) = 1x(x-2) + 7(x+4) = (x+4)(x-2)x^2 -2x +7x +28 = x^2 -2x +4x -8x^2 +5x +28 = x^2 +2x -83x +36 = 03x = -36x x= -12
Solve the quadratic inequality: x^2 - 5x + 4 < 0 | MyTutor x 2-5x+4 <0First we ignore the inequality and try to solve the equation x 2-5x+4=0, which we do via factorising (x-4)(x-1)=0. x = 4 or x=1We draw the graph using our solution, going through …
Expand x(x+4) - MyTutor You must expand the brackets and then handle each section separately x multiplied by x = x^2 x multiplied by 4 = 4x answer is x^2 + 4x Answered by Tutor125675 D. • Maths tutor 4978 Views
Solve x^2 = 4 (x – 3)^2 - 3)^2 | MyTutor x 2 =4(x-3) 2. To do this we first expand the brackets. Remeber anything squared means times it by itself (x-3) 2 =(x-3)(x-3) =x 2-6x+9. This makes the equation look like this x 2 =4(x 2-6x+9) …